Going beyond frontiers in household energy transition in Poland—a perspective - Kubiczek, Jakub; Hadasik, Bartłomiej; Krawczyńska, Dominika; Przedworska, Kornelia; Ryczko, Aleksandra (Frontiers in Energy Research, 2023)
Transition towards a cleaner and more sustainable environment is mainly driven by co-participation of households, whereas the residents’ transformation willingness is determined by various factors, including an environmentally-friendly attitude and greater public awareness. Simultaneously, the global push for a climate-neutral economy fuels the increasing emphasis on eco-consciousness and promotion of green investments. However, Poland still heavily relies on coal for energy production, despite the opportunities provided by the EU. Poland faces challenges in transitioning its households to cleaner energy sources, particularly due to historical conditions and the dominance of solid fuel boilers. This article shed light on the inefficiency of the energy transition process in Poland, presenting legal, economic, and social aspects. Despite multiple efforts, energy transition in Poland is not as buoyant as in other EU countries. Among the reasons for this phenomenon are the adverse behavior of residents, or government policies that favor the carbon-centric nature of the economy resulting in the low use of EU and state funds. This may lead to a continuation of the slower pace of change and eventually reaching the frontier of development in Poland’s energy transition. The multitude of campaigns and initiatives encouraging Poles to switch to green energy should be underscored, but due to their scant ecological awareness and orientation towards economic rather than ecological considerations, existing measures should be reviewed. In view of the above, to ensure an effective transition, it is necessary to recognize and clearly define the incentives that would induce Polish households to use climate-neutral energy sources.